PEMILIHAN KARIR SEBAGAI AKUNTAN PUBLIK BAGI MAHASISWA PERGURUAN TINGGI SWASTA DENGAN PENDEKATAN THEORY OF PLANNED BEHAVIOUR - Lukman, Hendro; Winata, Sugim (Jurnal Akuntansi, 2017)
The purpose of this study is to see how the attitude, subject norms, perceived behavior control and intention to behavior for a career as a public accountant in the perception of accounting students at private universities in Jakarta by using the approach of The Theory of Planned Behaviour (TPB). Data collected for processed were total of 106 questionnaires. Data processed by using Stata, showed that attitude, subject norms and perceived behavior control has a weak correlation and no significant effect among those variables, on student intention became public accountants, and to the behavior of a career as a public accountant through Ã‚Â intention as mediating variable. However, the relationship between intention on student become a public accountant to the behavior of a career as a public accountant has a strong relationship and have a significant impact. It can be concluded that the respondents' interest in working as a public accountant only temporarily as a stepping stone to other professions